Asian monsoon and oceanic circulation paced sedimentary evolution over the past 1, 500 years in the central mud area of the Bohai Sea, China. (5th February 2020) - Lyu, Wenzhe; Yang, Jichao; Fu, Tengfei; Chen, Yanping; Hu, Zhangxi; Tang, Ying Zhong; Lan, Jianghu; Chen, Guangquan; Su, Qiao; Xu, Xingyong; Chen, Shenliang
Abstract : Mud areas within China's marginal seas record critical information about historic environmental changes, which may have contributed to palaeoenvironmental processes and to understand their driving mechanisms. In this study, we investigated the sedimentary characteristics of a gravity core from the Bohai Sea central mud areas, to reveal the interactions between oceanic and climatic changes over the past 15 centuries. Sedimentary and mineral records indicated that the depositional environment and sediment sources were relatively stable, in which the East Asian Summer Monsoon (EASM) and Yellow Sea Warm Current (YSWC) variability can be derived. Based on these results, we found that the winter Arctic Oscillation (wAO) was negatively correlated with the coupled EASM and YSWC changes, namely, a negative (positive) relationship between EASM and YSWC during a positive (negative) wAO. We therefore suggest that over the past 15 centuries, Arctic winter climates may have modulated palaeoenvironmental changes over East Asia continental shelves, via teleconnections with the El Ninõ‐Southern Oscillation (ENSO) and the Kuroshio Current.